(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
This study investigated the effects of nanosuspension and inclusion complex techniques on in vitro trypsin inhibitory activity of naproxen—a member of the propionic acid derivatives, which are a group of antipyretic, analgesic, and non-steroidal anti-inflammatory drugs. Nanosuspension and inclusion complex techniques were used to increase the solubility and anti-inflammatory efficacy of naproxen. The evaporative precipitation into aqueous solution (EPAS) technique and the kneading methods were used to prepare the nanosuspension and inclusion complex of naproxen, respectively. We also used an in vitro protease inhibitory assay to investigate the anti-inflammatory effect of modified naproxen formulations. Physiochemical properties of modified naproxen formulations were analyzed using UV, IR spectra, and solubility studies. Beta-cyclodextrin inclusion complex of naproxen was found to have a lower percentage of antitryptic activity than a pure nanosuspension of naproxen did. In conclusion, nanosuspension of naproxen has a greater anti-inflammatory effect than the other two tested formulations. This is because the nanosuspension formulation reduces the particle size of naproxen. Based on these results, the antitryptic activity of naproxen nanosuspension was noteworthy; therefore, this formulation can be used for the management of inflammatory disorders.